REPRESENTATION OF ISLAM IN ENGLISH ONLINE MEDIA: A LIBRARY-BASED DISCOURSE STUDY FOR ISLAMIC COMMUNICATION PERSPECTIVES - Maulidah, Idah; Maysharani, Tias (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
The manner in which Islam and Muslims are portrayed within English-language online media has become one of the most consequential issues in contemporary Islamic communication discourse. Persistent patterns of misrepresentation, stereotyping, and selective framing in mainstream Western digital media outlets have contributed to the construction of distorted public perceptions of Islam globally, with far-reaching implications for Muslim communities, interfaith relations, and the practice of da'wah in the international arena. This study aims to systematically examine the dominant patterns of Islamic representation in English online media, to analyze the discursive mechanisms through which such representations are produced and sustained, and to evaluate these findings through the theoretical lens of Islamic communication perspectives. Employing a systematic library-based research methodology, this study reviewed a curated body of scholarly literature comprising academic books published within the last five years and peer-reviewed articles from nationally accredited and internationally reputable journals published within the last three years. The review and analysis were guided by critical discourse analysis frameworks and Islamic communication theory. The findings reveal three predominant representational patterns in English online media: the securitization framing of Islam as an inherent threat to Western liberal order, the homogenization of Muslim identities that erases intra-Muslim diversity, and the episodic rather than thematic framing of Muslim experiences. From the vantage point of Islamic communication studies, these patterns are understood as manifestations of deep-seated Orientalist epistemologies that continue to shape media production in the digital age. The study concludes by offering a conceptual framework for counter-narrative da'wah strategies that can effectively address these representational challenges